Students’ Strategies of Receiving Higher Education in the Context of the Bologna Process (on the example of SU-HSE) - Tatyana Baranova; Yuliya Muratova; Yuliya Ovchinnikova (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The problems that Russian colleges face when they change to the «Bachelor Studies + Master Studies» system from the traditional 5-year cycle is usually analyzed from the viewpoint of the organization of the educational process. This article attempts to consider this same problem from a student’s standpoint. Empirical material collected in the Higher School of Economics showed that the strategies adopted by students (their choice of final degree) differ depending on the year of studies and the faculty where they study. However, interest is shown not to the entire system, but rather only to the Masters program, as students believe Bachelors diplomas not to be sufficient for the job market. The readiness of students to integrate into a unified European educational space is largely influenced by how well they are informed about the changes.